Trial of ORG 10172 in Acute Stroke Treatment (TOAST) Classification and Vascular Territory of Ischemic Stroke Lesions Diagnosed by Diffusion‐Weighted Imaging - Chung, Jong‐Won; Park, Su Hyun; Kim, Nayoung; Kim, Wook‐Joo; Park, Jung Hyun; Ko, Youngchai; Yang, Mi Hwa; Jang, Myung Suk; Han, Moon‐Ku; Jung, Cheolkyu; Kim, Jae Hyoung; Oh, Chang Wan; et al. (Journal of the American Heart Association, 2014)
Background The association between the location and the mechanism of a stroke lesion remains unclear. A diffusion‐weighted imaging study may help resolve this lack of clarity. Methods and Results We studied a consecutive series of 2702 acute ischemic stroke patients whose stroke lesions were confirmed by diffusion‐weighted imaging and who underwent a thorough etiological investigation. The vascular territory in which an ischemic lesion was situated was identified using standard anatomic maps of the dominant arterial territories. Stroke subtype was based on the Trial of ORG 10172 in Acute Stroke Treatment, or TOAST, classification. Large‐artery atherosclerosis (37.3%) was the most common stroke subtype, and middle cerebral artery (49.6%) was the most frequently involved territory. Large‐artery atherosclerosis was the most common subtype for anterior cerebral, middle cerebral, vertebral, and anterior and posterior inferior cerebellar artery territory infarctions. Small vessel occlusion was the leading subtype in basilar and posterior cerebral artery territories. Cardioembolism was the leading cause in superior cerebellar artery territory. Compared with carotid territory stroke, vertebrobasilar territory stroke was more likely to be caused by small vessel occlusion (21.4% versus 30.1%, P<0.001) and less likely to be caused by cardioembolism (23.2% versus 13.8%, P<0.001). Multiple‐vascular‐territory infarction was frequently caused by cardioembolism (44.2%) in carotid territory and by large‐artery atherosclerosis (52.1%) in vertebrobasilar territory. Conclusions Information on vascular territory of a stroke lesion may be helpful in timely investigation and accurate diagnosis of stroke etiology.